Plasmodium falciparum SERA protein peptide analogues having short helical regions induce protection against malaria (2003)
Three Plasmodium falciparum serine repeat antigen (SERA) protein peptides were studied by NMR and structure calculations being done in 70:30 water:trifluoroethanol solution. Peptide 22834 was shown to be immunogenic and protective against malaria in Aotus monkeys, whilst native peptide 6737 and its analogue 14096 did not present protection against the disease in these monkeys. Results showed a relationship between these peptides’ secondary structure and their function as immunogen against malaria.